VAKHTANG VI ON THE SENTINEL OF THE HISTORICAL-LITERARY BOUNDARY (Conferencea, 2024)
The 18th century is a rather difficult period both in the world history and in the history of our country. Austria, Russia had been active on the world chess board (we are not talking about England-France competition on the mainland or in colonial politics) and other political processes have taken place. This period in the history of our country is marked: Georgia is divided (3 political units and separate Samtskhe-Saatabago), to this is added the struggle of two Muslim states in the Caucasus region, including Georgia. During these difficult and important issues, Vakhtang VI becomes the ruler of Georgia, a person who stood as a guard of the country, despite the failure in the foreign arena. A person who played a great role in the strengthening and development of Georgian culture and education.